Adaptive control for degree of refrigerant superheat in a direct expansion air conditioning system under variable speed operation. (February 2019) - Yan, Huaxia; Xia, Yudong; Deng, Shiming
Abstract: Direct expansion air conditioning systems are widely installed in small-to medium- scale buildings due to their advantages of simple configuration, high energy efficiency and low cost to own and maintain. The two main targets of air conditioning operation include improving the system operational efficiency and energy efficiency. Stable system operational efficiency is directly related with the operation of electronic expansion valves and degree of superheat at the outlet of evaporator. In this paper, an adaptive DS controller is developed to improve the system operational efficiency based the experimental performance of a DX A/C system and reported. The adaptive DS controller is designed to seasonably regulate the degree of superheat when the system is subjected to changes in operating conditions. Experimental controllability test results show that the controller has a very stable behavior, allowing an effective and fast control of the DS setting.